The invisible geography of affection, behind the imprint of being in space (Pulso. Revista de educación, 2002)
Space is not merely a geometric concept, but rather a fundamental element that contains life, memories, desires, and dreams.  The extent to which a human being can adapt to their surroundings significantly influences their identity, as space becomes an integral part of the individual.  The places where we are, with which time forms and cements our existence, encircle not only our physical bodies but also our feelings.  For this reason, it is crucial and pressing that we contemplate the nature and authenticity of the spaces we occupy.